En souvenir de Bruno - Geoffrey C. Bowker (Revue d'anthropologie des connaissances)
The author recounts their first encounter with Bruno Latour in 1980, marking the beginning of a profound intellectual and personal relationship. Latour's generosity and innovative thinking deeply influenced the author's academic journey, despite their ambivalence toward actor-network theory. Latour’s work, characterized by its generative and inclusive approach, contrasted with the more defensive academic norms. While the author critiqued Latour's incomplete exploration of ontology, they admired his creative spirit and his ability to connect people and ideas, leaving a lasting legacy of joy and inspiration.